The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fcvm.2022.895797
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Revealed That Mitochondrial Function Contributed to the Protective Effect of Herba Siegesbeckiae Against Cardiac Ischemia/Reperfusion Injury

Abstract: BackgroundMyocardial ischemia/reperfusion (I/R) injury is the main obstacle to percutaneous coronary intervention, lacking effective therapeutic measures in a clinical setting. Herba Siegesbeckiae (HS) is a traditional herb with multiple pharmacological activities and evidence of cardiovascular protection. However, few data are available regarding the role of HS in cardiac I/R. This study aimed to explore the effect and underlying mechanism of HS aqueous extract on cardiac I/R injury.Materials and MethodsHerba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…can inhibit oxidative stress and subsequently resist damage due to cardiac ischemia/reperfusion by restoring mitochondrial ultrastructure and electron transport chain complex function through the upregulation of Bdh1 expression. 39 Xu et al found that the overexpression of Bdh1 could attenuate high-fat diet-induced liver damage by inhibiting oxidative stress and apoptosis. 40 Our results showed that Bdh1 overexpression reduced oxidative stress and inflammatory responses in macrophages and that AAV-mediated Bdh1 overexpression reduced vascular inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…can inhibit oxidative stress and subsequently resist damage due to cardiac ischemia/reperfusion by restoring mitochondrial ultrastructure and electron transport chain complex function through the upregulation of Bdh1 expression. 39 Xu et al found that the overexpression of Bdh1 could attenuate high-fat diet-induced liver damage by inhibiting oxidative stress and apoptosis. 40 Our results showed that Bdh1 overexpression reduced oxidative stress and inflammatory responses in macrophages and that AAV-mediated Bdh1 overexpression reduced vascular inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…52 CVDs are the cardiometabolic alterations for which more in vivo studies have explored how polyphenols could modulate the NLRP3 inflammasome, with a total of 18 studies on the topic (17 preclinical and 1 clinical), whose main findings are summarized in Table 2. [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] Regarding the pre-clinical trials, the two most commonly selected animal models corresponded to the middle cerebral artery occlusion/reperfusion model (MCAO/R) in rats 56,59,61,[64][65][66][67] and the myocardial ischemia/reperfusion model (MI/R) in rats or mice. 53,55,58,69,70 Other different…”
Section: Cardiovascular Diseases (Cvds)mentioning
confidence: 99%
“…[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] Regarding the pre-clinical trials, the two most commonly selected animal models corresponded to the middle cerebral artery occlusion/reperfusion model (MCAO/R) in rats 56,59,61,[64][65][66][67] and the myocardial ischemia/reperfusion model (MI/R) in rats or mice. 53,55,58,69,70 Other different…”
Section: Cardiovascular Diseases (Cvds)mentioning
confidence: 99%
See 2 more Smart Citations